Ursolic acid elicits intrinsic apoptotic machinery by downregulating the phosphorylation of AKT/BAD signaling in human cisplatin‑resistant oral cancer CAR cells - Chen, Chin‑Fu; Yang, Jai‑Sing; Chen, Wen‑Kang; Lu, Chi‑Cheng; Chiang, Jo‑Hua; Chiu, Hong‑Yi; Tsai, Shih‑Chang; Juan, Yu‑Ning; Huang, Hao‑Jen; Way, Tzong‑Der (Oncology reports, 2018)
Oral squamous cell carcinoma (OSCC) is a type of cancer with high morbidity and mortality rates worldwide; it also demonstrates chemotherapeutic resistance. Triterpenoid ursolic acid has been shown to exhibit various biological activities and anticancer effects in several preclinical studies. In our previous study, human cisplatin‑resistant oral cancer CAR cells were established, and the present study aimed to further examine the effects of ursolic acid on CAR cells. The results revealed that ursolic acid inhibited CAR cell viability, as determined using a 3‑(4,5‑dimethylthiazol‑2‑yl)‑2,5‑diphenyltetrazolium bromide assay. Ursolic acid‑induced cell death was mediated through a caspase‑dependent pathway, determined with the pan‑caspase inhibitor, z‑VAD‑fmk. Ursolic acid also increased the activities of caspase‑3 and caspase‑9 in CAR cells, determined by a colorimetric assay. Specifically, the production of reactive oxygen species and loss of mitochondrial membrane potential, detected by flow cytometry, were observed in the ursolic acid‑treated CAR cells. The apoptosis‑associated signaling showed that ursolic acid decreased the phosphorylation of AKT (Ser473) and B‑cell lymphoma 2 (Bcl‑2)‑associated agonist of cell death (BAD; Ser136), and the protein levels of Bcl‑2 and Bcl‑extra large (Bcl‑xL), and increased the expression of BAD and Bcl‑2‑associated X (Bax) protein in CAR cells. In summary, the results supported the potential application of ursolic acid against drug‑resistant oral carcinoma and to improve oral anticancer efficacy in the near future.